2016
DOI: 10.15171/jcs.2016.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NICU Department Orientation Program on Mother’s Anxiety: a Randomized Clinical Trial

Abstract: Introduction: Neonatal intensive care unit induces the high level of anxiety for mothers. The aim of this study was to evaluate the effectiveness of NICU orientation program on the anxiety of mothers who had preterm newborns hospitalized in NICU. Methods: This study was a randomized clinical trial (three parallel groups). Participants included 99 mothers with preterm newborns hospitalized in NICU of Al- Zahra hospital, affiliated to Tabriz University of Medical Sciences in 2015. Mothers were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“… 31 Valizadeh et al, reported that using orientation program through watching a film or reading a booklet for mothers who had preterm delivery, before entering to NICU; is an effective strategy for reducing the maternal anxiety. 32 …”
Section: Discussionmentioning
confidence: 99%
“… 31 Valizadeh et al, reported that using orientation program through watching a film or reading a booklet for mothers who had preterm delivery, before entering to NICU; is an effective strategy for reducing the maternal anxiety. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Confirming the results of the research, in the study of Ghodrati et al [ 38 ], training neonatal care during a 45-60-minute session to mothers of premature infants significantly reduced their anxiety levels in 10 days after delivery ( P = 0.002). In another study, Valizadeh et al [ 39 ] placed 99 mothers of preterm infants into one of three groups: film, booklet, and control. The mothers completed the State- Trait Anxiety Inventory before entering the neonatal intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Although such a deficiency constitutes a limitation of this study, the technologysupported orientations foundin the literature aimed to relieve the concerns of inpatients in surgical-internal clinics before any procedure. 2,7,23,24,37,38,40 According to the results of these studies, the concerns of inpatients arise from uncertainties about the future or informational deficiencies regarding the procedures following their first-time admission to psychiatric clinics. These results are similar to those of this study.…”
Section: Patients Who Came On Mondays and Wednesdays Experimental Group (16)mentioning
confidence: 99%